The Influence of Leadership Style, Motivation, and Work Discipline on Employee Performance PT. Perkebunan IV Kebun Adolina Nusantara Perbaungan - Suparman; Erni; Zetta; Hobes; Yovie Ernanda (Jurnal Mantik, 2021)
This study aims to analyze the influence of leadership style, motivation, and work discipline on employee performance at PT Perkebunan IV Kebun Adolina Nusantara Perbaungan, the study uses a quantitative approach, in collecting data using questionnaires, interviews, and documentation, the population of all employees is 65 people, and The results showed that leadership style, discipline had a positive and significant effect, while the motivation variable had a positive and insignificant effect. Simultaneous testing shows that all variables of leadership style, motivation and work discipline have a positive and significant impact on the performance of PT Perkebunan IV Kebun Adolina Nusantara Perbaungan. While the results of the coefficient of determination show that 25, 4% variation in performance table (Y). Meanwhile, 74.6% are other independent variables that are not explained in this study.